(untitled) (Revista da Faculdade de Odontologia - UPF, 2015)
Aim: to evaluate the effects of different instrumentation on smear layer formation in the apical third of mesiobuccal roots of 90 upper molars by scanning electron microscopy (SEM). Methods: Three groups were formed on the basis of the technique used: hand instrumentation, K3 rotary system and with a reciprocating NSK handpiece. The groups were subdivided into 3 subgroups according to the size of the apical stop preparation: #30, #35, or #40 file. After preparation, roots were sectioned transversely, separating the apical thirds of the remainder of the roots; these thirds were split into halves and were prepared for SEM. The smear layer formation on the surface of the root canal and in the dentinal tubules was evaluated at 1,000Ã— magnification and scored. Data were analyzed using the Kruskal–Wallis test and Dunn’s test (p < 0.05). Results: The increase of the diameter in apical preparation did not enhance the formation of the smear layer from dentinal walls. Conclusion: Regardless of the technique and diameter of the apical instrument employed in the preparation, no dentinal wall free of smear layer was observed.